2015
DOI: 10.1044/2014_ajslp-13-0148
|View full text |Cite
|
Sign up to set email alerts
|

Intraword Variability in Typical Speech Development

Abstract: Variability is prevalent in the speech of typically developing 2- and 3-year-olds and was observed even in the oldest children. Future work is needed to determine at what age this type of phonemic variability is no longer prevalent in typical speech development. Clinicians should use caution in interpreting the presence of intraword variability as indicative of specific subtypes of speech disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(81 citation statements)
references
References 23 publications
5
74
2
Order By: Relevance
“…This indicates that these tasks do contribute to the diagnostic differentiation between typical and atypical development. In studies on speech development, speech variability, as assessed with the WR and NWR tasks, has been found to be relatively high in young typically developing children (2-and 3-year-olds; Sosa, 2015), and such variability decreases with age (Holm, Crosble, & Dodd, 2007). In a previous study (van Haaften et al, 2019), we also found minor decreases of the PWV with age.…”
Section: Discussionsupporting
confidence: 52%
“…This indicates that these tasks do contribute to the diagnostic differentiation between typical and atypical development. In studies on speech development, speech variability, as assessed with the WR and NWR tasks, has been found to be relatively high in young typically developing children (2-and 3-year-olds; Sosa, 2015), and such variability decreases with age (Holm, Crosble, & Dodd, 2007). In a previous study (van Haaften et al, 2019), we also found minor decreases of the PWV with age.…”
Section: Discussionsupporting
confidence: 52%
“…‘wabbit’ and ‘rabbit’) is said to exhibit variability that signals the transition toward a more stable and mature pattern. In typically developing children, segmental variability decreases with age (Holm, Crosbie, & Dodd, 2007; Sosa, 2015) as children become more systematic in their application of phonological regularities.…”
Section: Variability In Development and Disordersmentioning
confidence: 99%
“…For instance, in a recording of the Dutch-speaking boy Maarten at age 1;11.08 (years;months.days), the child produced the proper name "Dominiek" /dominik/ in at least five different ways: [dɔmənik], [dɔmnik], [mik], [əmik], [mənik], [dənik] (Gillis, 2000). This type of intraword or token-to-token variability in typically developing children with normal hearing's (NH) early word productions has received ample attention in the literature (e.g., Sosa, 2015). Whether this phenomenon is equally frequent and develops in a similar fashion in children with congenital hearing impairments who received a cochlear implant (CI) in comparison with their peers with NH has hardly been investigated.…”
mentioning
confidence: 99%